Effect of different drying methods on bioactive potential and nutrients of medlar fruit - Begüm Arkain; Ilknur Alibas (Scientific Reports)
Abstract In the study, medlar samples were dried using natural drying in the shade at 25 °C, convective drying at 40, 50, and 60 °C, microwave drying at 200, 400, and 600 W, and combined drying with a combination of convective drying temperatures and microwave output powers. In order to precisely determine the effect of the method used, each drying technique was considered in a comprehensive framework. The moisture content of medlar was reduced from 74.07 to 11.75%. While the drying process took the longest time in shade drying, the drying process took the shortest time at 600 W–60 °C. The closest results to fresh product in terms of total protein content were found at 400 W. In addition, phosphorus, potassium, sodium and copper contents were maximised at 600 W–60 °C. The maximum contents for magnesium and manganese were 400 W–40 °C, while for zinc, it was 600 W–40 °C. After fresh products, the highest calcium was obtained at 600 W, and the highest iron was obtained at 200 W. The bioactive potential of medlar samples was evaluated in terms of extractable, hydrolysable and bioaccessible phenolic fractions by total phenolic content and antioxidant capacity assays. In terms of TPC, the bioaccessibility of the samples was highest when natural drying was used. The highest bioaccessibility values for ABTS, DPPH and CUPRAC were obtained at natural drying, 200 W–50 °C and 400 W–60 °C, respectively. As a result, DPPH was the most suitable antioxidant capacity determination method due to high results.